A Aula de Geometria Descritiva da Faculdade de Matemática e a sua Coleção de Modelos de Olivier - Carlos Tenreiro (Documentos, 2019)
At the Department of Mathematics of the Faculty of Science and Technology of the University of Coimbra we can observe a collection of five geometric models, mounted on boxes or wooden brackets, in all analogous to the idealized by Théodore Olivier (1793-1853) to expose some of the contents of the descriptive geometry. Deprived of his first function of teaching support, the models of descriptive geometry continue to carry out the important mission of reminding us of an already distant past but we must not forget. This is also the main objective of this text, dedicated to the class of descriptive geometry of the Faculty of Mathematics of the University of Coimbra and his collection of Olivier models.